GAROWAĆ – O PEWNYM MAŁO ZNANYM, A WIELOZNACZNYM CZASOWNIKU - OSOWSKI, BŁAŻEJ (Slavia Occidentalis, 2020)
Garować is a word which at present belongs primarily to the colloquial variety of the Polish language. Wielki słownik języka polskiego [The Great Dictionary of the Polish Language] mentions 6 meanings of the verb. However, this number does not exhaust the range. The goal of the article is to present the scope of the contemporary meanings of the word. To this end, an online questionnaire was distributed which produced 1,302 replies related to the subject of my interest. The article presents excerpted meanings arranged by prevalence (taking into consideration, if relevant, data of geographic and sociological nature). Next, a scheme of the meanings’ affiliation was suggested. Therefore, this text connects with the works using both the achievements of lexicography as well as empirical research into semantics, based on the ndata from the questionnaires.